ab=256,ab=256,\frac{a}{b} = \frac{{25}}{6}{\text{,}} then the value of a2−b2a2+b2" role="presentation">a2−b2a2+b2a2−b2a2+b2\frac{{{a^2} - {b^2}}}{{{a^2} + {b^2}}} is?" /> ab=256,ab=256,\frac{a}{b} = \frac{{25}}{6}{\text{,}} then the value of a2−b2a2+b2" role="presentation">a2−b2a2+b2a2−b2a2+b2\frac{{{a^2} - {b^2}}}{{{a^2} + {b^2}}} is?" /> ab=256,ab=256,\frac{a}{b} = \frac{{25}}{6}{\text{,}} then the value of a2−b2a2+b2" role="presentation">a2−b2a2+b2a2−b2a2+b2\frac{{{a^2} - {b^2}}}{{{a^2} + {b^2}}} is?" />
Post your Comments